Consumption of treated water in the cities of Governador Valadares and Teófilo Otoni between 2013 and 2017 (International Journal of Geoscience, Engineering and Technology, 2020)
The issue of water consumption in Brazil has been increasingly valued as it reduces its availability and quality. The National Sanitation Information System is considered a relevant database with registered information and indicators. Governador Valadares is a municipality located in the Rio Doce basin that suffered from the breach of the bottom dam in November 2015. Teófilo Otoni has Rio de Todos os Santos as the main responsible for the city's water supply. The objective of this work was to identify from the SNIS data or the panorama of water consumption between 2013 and 2017, how to compare the population served with water consumption, the volume produced and the volume treated by the ETAs, or the micro-measured volume with an amount of active residential use of micro-measured water, and the volume of daily water consumption per capita with the reality of each municipality. As statistics shown in the municipality of Governador Valadares show an increase in its total population, also having an increase in the population served with water consumption by SAAE, they had a decrease in water consumption per inhabitant / day from 2015, which coincide with the year of the Fundão dam rupture. Teófilo Otoni also showed a population increase, but COPASA did not keep up with this increase, it showed a reduction in the total population served by him, but there was an increase in the number of years of water consumption per inhabitant / day.
Keywords: Basic sanitation; Water supply; Water consumption; SNIS